2020
DOI: 10.21831/pep.v24i1.28037
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the implementation of authentic assessments in junior high school English lesson

Abstract: This study aims to describe the quality and implementation of authentic assessments planning of English subject at junior high schools in Yogyakarta. This evaluation research used a discrepancy evaluation model. It was conducted at three public junior high schools in Yogyakarta which were pilot projects of the 2013 Curriculum, namely SMP Negeri 5, SMP Negeri 8, and SMP Negeri 15. The data in this study were obtained through documentation, interviews and questionnaires. The sample in this study were six English… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 4 publications
1
3
0
Order By: Relevance
“…The result of this study revealed that the enforcement of authentic assessment in both schools were nice. The finding was in accordance with the studies from Afriadi et al (2021), Ningsih & Wahyumiani (2020), Mursyida et al, (2020) and Rukmini & Saputri (2017) that claimed the usage of authentic asssessment in the class was great and can be another option to appraise students' speaking skills instead the traditional assessment. The similarities of this study with previous studies are the method and the subject of the research.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The result of this study revealed that the enforcement of authentic assessment in both schools were nice. The finding was in accordance with the studies from Afriadi et al (2021), Ningsih & Wahyumiani (2020), Mursyida et al, (2020) and Rukmini & Saputri (2017) that claimed the usage of authentic asssessment in the class was great and can be another option to appraise students' speaking skills instead the traditional assessment. The similarities of this study with previous studies are the method and the subject of the research.…”
Section: Discussionsupporting
confidence: 91%
“…The study explained that two English lecturers had been appliying authentic assessment in their classroom, but they did not implement it properly in speaking class yet. Studies from Ningsih & Wahyumiani (2020), Rahayu et al (2021), Rukmini & Saputri (2017), Inayah et al (2019) suported the finding. All of those studies revealed that the implementation of authentic assessment in schools had done by teachers, still they did not applied in appropriate way yet.…”
Section: Introductionmentioning
confidence: 83%
“…Hereafter, the most visible characteristic of young learners is that they like to play, which sometimes makes them unable to take learning seriously, especially if the learning is boring. If the learning cannot run with fun, young learner who have a short attention span can easily distracted with others more interesting (Ningsih, 2020). Considering this, the teacher must be smart in selecting media to provide a fun learning environment toward English for young learners to catch their attention to the learning.…”
Section: Methodsmentioning
confidence: 99%
“…Meanwhile, attention to the need for the growth of emotional and social intelligence still lacks in understanding, both in the learning process and in the process carried out in schools. The process of implementing the assessment of the result in schools, especially at the elementary school level so far, has only carried out assessments (Ningsih & Wahyumiani, 2020).…”
Section: Introductionmentioning
confidence: 99%